Brazilian infant dairy foods: mineral content and daily intake contribution. Issue 10 (9th August 2018) - Pimentel, Luana S.; Moraes, Jeremias; Luna, Aderval S.; Barros, Diego B.; Pimentel, Tatiana C.; Guimarães, Jonas T.; Silva, Hugo L.A.; Balthazar, Celso F.; Esmerino, Erick A.; Freitas, Mônica Q.; Ranadheera, C.S.; Silva, Marcia C.; et al.
Abstract : Purpose: The purpose of this paper is to investigate the mineral content of seven Brazilian infant dairy product categories (petit Suisse cheeses, fermented milks, yogurts, fermented dairy beverage, dairy dessert, Requeijão cremoso spreadable cheese and UHT dairy beverages) and estimate their contribution to daily intake. Design/methodology/approach: The composition of major (Ca, K, Mg, and Na) and trace (Pb, Cd, Cu and Mn) minerals was determined using Inductively Coupled Plasma Optical Emission Spectrometry. Furthermore, a comparative analysis of the mineral levels with the Reference Daily Intake (RDI) at different child development stages was carried out. Findings: High Ca levels were observed in petit Suisse (3.44±1.66 mg g −1 ), dairy dessert (3.88±0.02 mg g −1 ) and Requeijão cremoso (4.14±0.07 mg g −1 ). Dairy dessert presented the highest K level (2.57±0.07 mg g −1 ), while the Requeijão cremoso presented the highest Na content (4.78±0.10 mg g −1 ), and both products had the highest Mg contents (238.55±16.27 and 197.39±5.18 µ g g −1, respectively). Trace elements (Cd, Cu, Mn and Pb) were below the limit of detection for all commercial dairy foods. Among food products analyzed, petit Suisse cheese and dairy dessert can be considered good sources of calcium, while Requeijão cremoso is high in both calcium and sodium. Originality/value: This study is the first to analyze the mineral levels of several Brazilian infant dairy foods and the daily intake contribution during important child development stages. These findings provide valuable guidance for researchers and practitioners trying to develop healthy and nutritious dairy products for infants and children.